Development (paradigm) failures - Hodler, Roland; Dreher, Axel (Journal of development economics, 2013)
Over time, the international development community has advocated various development paradigms, but countries following these paradigms have often performed poorly. We provide an explanation for this poor performance. In our model, the political leader of a developing country chooses a policy and whether to implement it in an honest or corrupt manner. These choices affect domestic production and aid inflows. Production is high when productive capacity is high, and when the policy is appropriate in the country-specific circumstances and implemented honestly. Aid inflows are high when the policy is close to the paradigm. In equilibrium, countries with low productive capacity and high corruption resulting from weak political institutions follow the paradigm more closely. Hence, our model suggests that development paradigms have a tendency to fail because they are primarily followed by countries that would fail anyway. We provide empirical evidence in support of the main assumptions and results.